EFFECT OF DIETS BASED ON ALFALFA, BARLEY MEAL AND MINERAL BLOCK ON THE PRODUCTIVE PERFORMANCE OF GUINEA PIGS - Quintana M., Erika (2013)
The effect of feed supplementation with barley meal and mineral block on body weight gain, feed intake, feed conversion index, slaughter age, production cost and profit/cost ratio was evaluated in guinea pigs fed with alfalfa. A total of 250 male weaned animals were used in a completely randomized block design with a 2x2 factorial arrangement (barley meal x mineral block) and one additional treatment for contrast (balanced diet).Barley meal supplementation significantly improved (p<0.05) body weight gain, feed intake, feed conversion index, benefit cost ratio and decreased slaughter age while mineral block supplementation only decreased slaughter age (p<0.05). On the other hand,plain forage without supplements and forage plus barley meal showed the best economic results.